EXPERIENCE OF MOTHERS IN IMPLEMENTING MEAL PLANS TOWARDS THE INCIDENCE OF STUNTING IN TODDLERS AT BANGUNGALIH HEALTH CENTER - Chikmah, Adevia Maulidya; Harnawati, Riska Arsita; Qudriani, Meyliya (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Indonesia still has a fairly high stunting prevalence rate of 24.4% which is still above the standard tolerated by WHO, which is below 20%. Meanwhile, in Central Java, the stunting rate reached 20.9% and based on family data, 43.05% of families were at risk of stunting. In the Bangungalih Health Center area, there were 3,437 toddlers and 471 toddlers experiencing stunting. Every day toddlers need balanced nutrition such as carbohydrates, proteins, fats, vitamins and minerals, the nutritional intake is obtained from the food consumed by toddlers. According to the Minister of Health of the Republic of Indonesia No. 14 of 2014, food management or food management is a series of activities starting from menu planning, planning food needs, budgeting, procurement of food ingredients, distribution, recording, reporting and evaluation. The purpose of this study was to identify the experiences of mothers under five in implementing meal plans for stunting. The research method used was an analytical survey by analyzing the experiences of mothers under five in implementing meal plans on the risk of stunting in the Bangungalih Health Center area. The population is mothers who have toddlers, with the sampling technique that is accidental sampling. The number of respondents was 20 people. The results of the study show that there is a link between financial planning and menu planning with the incidence of stunting. Meanwhile, planning for food procurement and food processing is not related to stunting.